Measuring affective reactivity in individuals with autism spectrum personality traits using the visual mismatch negativity event-related brain potential - Gayle, Leigh C.; Gal, Diana; Kieffaber, Paul D. (Frontiers in Human Neuroscience, 2012)
The primary aim of this research was to determine how modulation of the visual mismatch negativity (vMMN) by emotionally laden faces is related to autism spectrum personality traits. Emotionally neutral faces served as the standard stimuli and happy and sad expressions served as vMMN-eliciting deviants. Consistent with prior research, it was anticipated that the amplitude of the vMMN would be increased for emotionally salient stimuli. Extending this finding, it was expected that this emotion-based amplitude sensitivity of the vMMN would be decreased in individuals with higher levels of autism spectrum personality traits as measured by the Adult Autism Spectrum Quotient (AQ). Higher AQ scores were associated with smaller amplitudes of the vMMN in response to happy, but not sad emotional deviants. The fact that higher AQ scores were associated with less sensitivity only to happy emotional expressions is interpreted to be consistent with the negative experience of social interactions reported by individuals who are high on the autism spectrum. This research suggests that that the vMMN elicited by deviant emotional expressions may a useful indicator of affective reactivity and may be related to social competency in ASD.